Effect of fungicides on the enzymatic activity of the antioxidant system and the chlorophyll content in lupine plants during seed dressing - O. Borzykh; O. Tsurkan; L. Chervyakova; T. Panchenko (Карантин і захист рослин)
Goal. The effect of fungicides on the dynamics of the activity of peroxidase, catalase (CAT) and chlorophyll content in lupine plants during seed dressing has been established.